2000
DOI: 10.1080/00343400050085675
|View full text |Cite
|
Sign up to set email alerts
|

Regional Size, Regional Specialization and the FLQ Formula

Abstract: FLEGG A. T. and WEBBER C. D. (2000) Regional size, regional specialization and the FLQ formula, Reg. Studies 34 , 563- 569. In examining how regional size might affect regional input-output coefficients, MCCANN and DEWHURST, 1998, raise some concerns about our FLQ formula for estimating such coefficients from national data. In particular, they point to the need to consider regional specialization when modelling regional economies. However, our empirical work using Scottish data shows that the inclusion of a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
13

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(115 citation statements)
references
References 7 publications
1
101
0
13
Order By: Relevance
“…Such cases are catered for by the augmented FLQ (AFLQ), which includes a regional specialization term. However, the empirical evidence suggests that this more complex adjustment formula does not yield significantly better results (Flegg and Webber, 2000;Bonfiglio and Chelli, 2008;Flegg and Tohmo, 2011).…”
Section: Use Of Location Quotientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such cases are catered for by the augmented FLQ (AFLQ), which includes a regional specialization term. However, the empirical evidence suggests that this more complex adjustment formula does not yield significantly better results (Flegg and Webber, 2000;Bonfiglio and Chelli, 2008;Flegg and Tohmo, 2011).…”
Section: Use Of Location Quotientsmentioning
confidence: 99%
“…This evidence includes studies using survey-based data for Peterborough (Flegg et al, 1995), Scotland (Flegg and Webber, 2000), one Finnish region (Tohmo, 2004), all Finnish regions (Flegg and Tohmo, 2011), along with the Monte Carlo study by Bonfiglio and Chelli (2008), who examined 400,000 sectoral output multipliers. On the other hand, Riddington et al (2006) found the FLQ to be unhelpful, albeit on the basis of findings pertaining to a single sector in one Scottish region (Flegg and Tohmo, 2011).…”
Section: Performance Of the Flqmentioning
confidence: 99%
“…This is achieved by utilising locally (SA2) specific business turnover data and employment and income data from the latest census to disaggregate national and state-level input-output and GHG data [49]. Flegg's adjusted location quotient method [50,51] is employed as a non-survey method and a modified RAS method is used for re-balancing the MRIO table [39,52]. Three GHGs were considered for the present analysis: carbon dioxide, methane and nitrous oxide.…”
Section: Methodology and Datamentioning
confidence: 99%
“…Thus, the optimal range of δ can be determined by reviewing the literature. Based on studies of Flegg and Tohmo (2013) in Finland, Kowalewski (2012) in Germany, Flegg and Webber (2000) in Scotland and Bonofiglio and Chelli (2008), we can state that δ is between 0.1 and 0.3.…”
Section: Empirical Results Of Non-survey Methodsmentioning
confidence: 99%